How то help homeless animals - Chura, D. (ТДАТУ, 2018)
EN: The problems of homeless animals are under consideration. The author stresses that the problems of homeless animals are consequences of people attitude. The ways of changing homeless animals ’ situation are proposed. UK: Автор тез розглядає проблеми тварин, що опинилися на вулиці без укриття, господаря, їжі. Автор нагадує, що проблеми таких тварин - це наслідки ставлення до них людей. Автором запропоновано шляхи рішення цієї проблеми.
Keywords: проблеми тварин; homeless animals; problems of homeless animals are